Faktor-Faktor yang Mempengaruhi Kualitas Konstruksi Rumah Menengah dan Mewah di Surabaya - Ambrosius Mintardjo; Timoticin Kwanda; Jani Rahardjo (Program Studi Magister Teknik Sipil - Petra Christian University, 2019)
The quality factor is considered when people will buy a house. People are willing to pay more for good quality house, as it will have high value to resell. Hence, it is important to realize quality factor in construction. The respondent answered how was the house construction quality in Surabaya and factors affecting it. The result of this research found 8 expected factors that affects the middle and high-end landed house construction quality in Surabaya. These factors were budget allocation for quality management and occupational health and safety, comprehensive review to the architecture and structure design, supplier management, process management, human resource management, written working standard, customer satisfaction oriented, and proper construction specification and drawing. Out of 8 factor, there was only 1 factor that affects the most, it was proper construction specification and drawing. This research also found there was a difference in factors affecting middle & high-end landed house construction quality in Surabaya.